Barriers related to non-adherence in a mammography breast-screening program during the implementation period in the interior of São Paulo State, Brazil - René Aloisio da Costa Vieira; Tânia Silveira Lourenço; Edmundo Carvalho Mauad; Valter Gonçalves Moreira Filho; Stela Verzinhasse Peres; Thiago Buosi Silva; Maria do Rosário Dias de Oliveira Lattore (Springer, 2019)
Mammography is the best exam for early diagnosis of breast cancer. Developing countries frequently have a low income of mammography and absence of organized screening. The knowledge of vulnerable population and strategies to increase adherence are important to improve the implementation of an organized breast-screening program. A mammography regional-screening program was implemented in a place around 54.238 women, aged 40-69 years old. It was proposed to perform biannual mammography free of cost for the women. We analyze the first 2 years of the implementation of the project. Mammography was realized in 17.964 women. 42.1% of the women hadn't done de mammography in their lives and these women were principally from low socio-economic status (OR = 2.99), low education (OR = 3.00). The best strategies to include these women were mobile unit (OR = 1.43) and Family Health Program (OR = 1.79). The incidence of early breast tumors before the project was 14.5%, a fact that changed to 43.2% in this phase. Multivariate analysis showed that the association of illiterate and the mobile unit achieve more women who had not performed mammography in their lives. The strategies to increase adherence to mammography must be multiple and a large organization is necessary to overpass the barriers related to system health and education.